Melukis sebagai Terapi Diri Mental Illness - Haniatus Sa’adah (Texture:Art and Culture Journal, 2022)
Art therapy is one type of the therapy which done through a creative process on the creation of a work of art as an effort to relieve the inner conflicts or repressed emotions in someone who suffers from health  problem  such  as  mental  illness.  The  aim  of  this  study  project  under  the  title  “Painting  as  Self- Therapy for Mental Illness” is to create an abstract  paintings based on inner experience as self-therapy for mental illness. In addition, the act of counseling routinely with a psychiatrist and drug therapy is being undertaken by the author. In this study project, the author creates a painting in an abstract-expressionistic style that is direct and spontaneous, with or without special considerations regarding the application of the visual concept of painting in his work, providing the author’s subjectivity in his work can be fulfilled absolutely. The abstract painting itself really emphasizes the expression of emotions through free strokes, line and colors which that is appropriate or suitable for art therapy medium; by using ink and acrylic paint on various types of paper such as; linen paper, recycled paper, and watercolor paper. The author also uses the direct method on painting the creative works or the paintings done by the act of spontaneously, quickly, and full of intuition with either wet or dry techniques. From the process of making this study project, the author was able to produce hundreds of works which later those selected, sorted, and arranged into a panel or an independent painting which concluded into total of 14 works with spontaneous, firm, textural, and magical line expressions. Through art therapy by working on abstract-expressionism style of painting, the author feels the psychological impact which leads into an atmosphere of happy inner-self, a relief, becomes more passionate, and a calmness which drives to organize life more optimistically, and also it is able to relieve the worries and pain that the author feels.